EFEKTIVITAS FOOT MASSAGE TERHADAP TINGKAT NYERI PADA PASIEN DI RUANG INTENSIVE CARE UNIT (ICU) RS PELITA ANUGERAH (Nursing Care Journal, 2024)
Background: Patients who experience pain in the ICU occured because it is related to their illness and medical and nursing treatmens that performed to the patient. Pain that is not treated immediately has a negative impact, namely the length of stay, the more costs, the worse the patients condition. Pain management in addition to fermacological therapy can also be done with non-pharmacological therapy, one of which is footmassage therapytechniques. Purpose: This study aims to determine the effectiveness of footmassage on pain levels in patients in the ICU room at PelitaAnugerah Hospital. Methods: The research design used was Pre Experimental design tipe one group pre test & post test on the intervention. The study was conducted in the ICU room of Pelita Anugerah Hospital in June 2021. The research sample was 20 respondents, taken by total sampling. The research instrument uses CPOT. Data analysis used bivariate. Results: From the Wilcoxon test, the p-value is 0.0001 (p value 0.05), then Ha is accepted, Ho is rejected. This means that the provision of footmassage therapy is effective in reducing the patient's pain level. Conclusion: For further researchers, this research can be used as a basis for complementary therapies in reducing the pain level of patients in the ICU.